Multi-objective optimization and price performance factor evaluation of polyaniline nanofibers-palm oil nanofluids for thermal energy storage application - Sofiah, A. G. N.; Pasupuleti, Jagadeesh; Samykano, Mahendran; N.F., Sulaiman; Z.A.C., Ramli; Reji Kumar, R.; Shahabuddin, S.; Pandey, A. K.; Tiong, S. K.; Koh, Siaw Paw (Elsevier, 2023)
The application of nanofluid in thermal energy storage technology has attracted interest among researchers in the development of novel nanofluids with high thermal conductivity behavior. Therefore, it is crucial to study the thermal physical behavior of formulated nanofluids prior to extend use in greener energy production. In this study, response surface methodology (RSM) is employed to optimize the density, viscosity and thermal conductivity behavior of formulated polyaniline-palm oil nanofluids. RSM based central composite design (CCD) is applied to extract the significant impact of temperature in the range of 30–60 °C and volume concentration of nanoadditives in the range of 0.01–0.5 vol% to the thermal physical properties of polyaniline-palm oil nanofluids and to generate empirical mathematical model for prediction purpose. Finally, the price performance factor of the studied polyaniline-palm oil nanofluids is evaluated for the first time in this research. Analysis of variance is employed to verify that the generated mathematical regression model is reliable. The formation of 45° angle line in the middle of the predicted vs actual data graph with acceptable R2 of 94.43% for density model, 99.43% for viscosity model, and 94.18% for the thermal conductivity model showing an excellent agreement of both predicted and actual data and verified the reliability of the generated regression equation for response prediction. Optimal density, viscosity and thermal conductivity of polyaniline-palm oil nanofluids found to be 0.8878 g/mL, 25.8251 mPa s and 0.2877 W/mK respectively with the critical parameters for temperature and volume concentration of polyaniline are 60 °C and 0.0347 vol% respectively. The PPF evaluation shows that the higher thermal conductivity of nanofluids are not economical. The formulated polyaniline-palm oil nanofluid evaluated properties expose the possibility of alternative advanced heat transfer fluid for thermal energy storage application due to their superior inherent qualities.